Formulation development of Carvedilol compression coated tablet. (August 2013) - Shah, Ritesh; Patel, Sachin; Patel, Hetal; Pandey, Sonia; Shah, Shailesh; Shah, Dinesh
<x xml:space="preserve">Abstract</x> Purpose: The aim of present research was to produce carvedilol compression coated tablet to provide biphasic drug release. Method: A compressed coated tablet made of a sustained release core tablet and an immediate release coat tablet. Both the core and the coat contained carvedilol. The sustained release effect was achieved with polymers (HPMC K4M and PEO WSR 205) to modulate the release of the drug. The powder blends for core and coat tablets were evaluated for angle of repose, bulk density, compressibility index, and drug content. Compressed coated tablets were evaluated for thickness, diameter, weight variation test, drug content, hardness, friability, disintegration and in vitro release studies. Result: The powder blends showed satisfactory flow properties, compressibility, drug content and all the tablet formulations showed acceptable pharmaco-technical properties. Carvedilol contained in the fast releasing component was released within 3 min, whereas the drug in the core tablet was released at different times up to 24 h, depending on the composition of the matrix tablet. The mechanism of drug release was fickian diffusion or anomalous behavior. Discussion: Batch F7, containing 10 mg PEO WSR 205 and 5 mg HPMC K4M, showed maximum similarity with theoretical profile and zero order drug release kinetic.